Daughters and sons of genocide perpetrators before the courts: experiences, obstacles and challenges (Quinto Sol, 2025)
In different historical periods, some daughters and sons of perpetrators from the last Argentine dictatorship, who condemn the repressive actions of their parents, have tried to bring their testimony before Courts of Justice to contribute what they knew from knew from being relatives about their crimes. But the Argentine Code of Criminal Procedure prohibits them from testifying against their parents, so their initiatives have been rejected on several occasions. However, a handful of testimonies have been admitted. Based on a series of individual and collective interventions by these individuals in Justice, over the past decade, the article unravels the legal and historical-political factors that enabled these actions, challenged the Code, and measures its social significance. It also highlights the singular influence of the collective ‘Historias Desobedientes’, since 2017. A qualitative methodology combining analysis of legal documentation, journalism, and interviews is employed to carry out this research.
Keywords: Dictatorship; Children of genocidal perpetrators; Justice; testimonies